Wheat transformation with HVA1 gene by microprojectile bombardment - Detvisitsakun, Chanitchote (Kansas State University, 2001)
To improve drought tolerance, a gene encoding a late embryogenesis abundant (LEA) protein, HVAJ, from barley (Hordeum vulgare L.) was introduced into winter wheat Jagger (hard red winter wheat) and Lakin (hard white winter wheat). The gene construction, containing HVA1 gene driven by the rice Actl promoter and the selectable marker gene, bar, under the control of CaMV35S promoter, was delivered to wheat embryogenic calli by means of microprojectile bombardment. One transgenic wheat plant of Jagger was obtained in this study. This plant survived in medium containing 5 mg/1 ammonium glufosinate during the tissue culture processes and has normal morphology. The plant tested positive for the PCR analysis of bar gene and was resistant to 0.1% (v/v) herbicide LibertyTM. Southern blot analysis showed the integration of bar and HVA1 gene into the genome of this plant. The 27 kDa of HVA1 protein also was detected in this plant as revealed by Western blot analysis.